Nacionalismo e música erudita de vanguarda no Brasil e Argentina: Camargo Guarnieri e Alberto Ginastera (1930-1960) - Ornaghi, Mário André [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
From the artistic careers of composers Alberto Ginastera and Camargo Guarnieri, this essay aims to analyze the consequences of nationalism and musical ―avant-garde‖ in Argentina and Brazil from 1930 to 1960. So, we will develop a focus compared between these two countries in a way that these trajectories can be analyzed in line with broader intellectual paradigms – including international ones - that ended up favoring certain aesthetic forms in different periods covered. We believe that the artistic options of Ginastera and Guarnieri are related to the musical past of their respective societies, hence the importance of discussing the Argentine and Brazilian cultural history, as well as the place and the strength that the nationalist movements and ―avantgarde‖ aesthetics forms found there

A partir das trajetórias artísticas dos compositores Alberto Ginastera e Camargo Guarnieri, este trabalho tem por objetivo analisar os desdobramentos do nacionalismo e das vanguardas musicais na Argentina e no Brasil, de 1930 a 1960. Desenvolveremos, assim, um enfoque comparado entre esses dois países de modo que essas trajetórias sejam analisadas em consonância com paradigmas intelectuais mais amplos – inclusive internacionais - que terminaram por privilegiar determinadas formas estéticas nos diferentes períodos abordados. Acreditamos, nesta medida, que as opções artísticas de Ginastera e Guarnieri estão relacionadas ao passado musical de suas respectivas sociedades, daí a importância de se discutir a história cultural argentina e a brasileira, assim como o lugar e a força que os movimentos nacionalistas e as estéticas de vanguarda lá encontraram
Keywords: Ginastera, Alberto - 1916-1983; Guarnieri, Camargo - 1907-1993; Vanguardismo; Arte e musica; Música e história; Música - História - Argentina; Arte e sociedade; Brasil - História - Séc. XX; History